Morphology and histology of the defensive glands of stick insect, Abrosoma johorensis - Zeti Aktar A.; Nurul Wahida O. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
This study was conducted to identify the morphology and histology of defensive glands of stick insect, Abrosoma johorensis (Phasmida: Aschiphasmatidae). Samples were collected from Mount of Ledang, Johor. Observation of gross morphology in-situ and ex-situ on the defensive gland of A. johorensis have been done using stereo microscope Carl Zeiss V12) connected to Canon EOS 1000D with LAS EZ software. Cell of A. johorensis’s defensive gland were stained using a special staining procedure that is Periodic Acid Schiff’s reagent and Alcian Blue method. Histological slides were viewed using light photomicroscope Carl Zeiss Axio Scope A1 with iSolutionLite v1.0 software. The defensive gland morphology showed that male individual of A. johorensis have a smaller size of gland compared to female individual. Histological study showed that the defensive gland structures consist of secretory epithelium and surrounded by layer of muscles known as longitudinal muscles and circular muscles. Observation on ultrastructure of the defensive gland was able to discover several components and organelle lies within the secretory epithelium region that might take part in the production of chemical secretion such as epithelial cells, pigment granules, ductules, vesicles, mitochondria, tracheols and secretory apparatus.